2013
DOI: 10.1007/s00109-013-1095-0
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin sensitizes human gastric cancer xenograft in nude mice to capecitabine by suppressing nuclear factor-kappa B-regulated gene products

Abstract: Chemoresistance remains a major problem in the treatment of gastric cancer patients. Hence, novel pharmacological agents that can overcome drug resistance are urgently required. Whether simvastatin can sensitize the gastric cancer to the antitumor effects of capecitabine in vitro and in vivo was investigated. The effect of simvastatin on the proliferation of gastric cancer cells was examined by mitochondrial dyeuptake 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide method, apoptosis by esterase st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 146 publications
(104 citation statements)
references
References 34 publications
2
102
0
Order By: Relevance
“…Apart from the studies mentioned above [38] that revealed that simvastatin treatment can decrease the tumor size in mice that had engrafted prostate cancer cells, many more such examples exist. Favorable effect of statins in vitro that were subsequently confirmed by studies in mice xenografts have also been demonstrated in the case of gastric [62], renal [63], and breast cancer [37,54], as well as for glioblastoma [64]. For example, it was shown that simvastatin inhibited the growth of the tumors derived from MDA MB 231 human breast cancer cell xenografts in mice [54].…”
Section: Studies In Vivomentioning
confidence: 85%
See 1 more Smart Citation
“…Apart from the studies mentioned above [38] that revealed that simvastatin treatment can decrease the tumor size in mice that had engrafted prostate cancer cells, many more such examples exist. Favorable effect of statins in vitro that were subsequently confirmed by studies in mice xenografts have also been demonstrated in the case of gastric [62], renal [63], and breast cancer [37,54], as well as for glioblastoma [64]. For example, it was shown that simvastatin inhibited the growth of the tumors derived from MDA MB 231 human breast cancer cell xenografts in mice [54].…”
Section: Studies In Vivomentioning
confidence: 85%
“…A study was carried out to investigate the use of simvastatin in a combination therapy with capecitabine in gastric cancer treatment [62]. It transcribed that simvastatin inhibited proliferation and enhanced apoptotic effect on cancer cells in vitro.…”
Section: Statins In Combination Therapiesmentioning
confidence: 99%
“…A549 cells were injected subcutaneously into the mice as described previously [55]. In brief, A549 cells were harvested from subconfluent cultures, washed once in serum-free medium, and resuspended in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…A number of NF-κB-regulated gene products, including cyclin D1, COX-2, etc. have been closely linked with the development of chemoresistance in gastric cancer [151]. Thus, a control of NF-κB activity might be a useful therapeutic strategy to augment conventional therapy and circumvent chemoresistance in gastric cancer patients.…”
Section: Nf-κb and Gastric Cancer Therapymentioning
confidence: 99%